STUDY OF TRADITIONAL KENDURI CEREMONY IN GUNUNGPAYUNG VILLAGE TEMANGGUNG CENTRAL JAVA - Ferrencia Calvina Effendi; Vishnuvardhana S. Soeprapto (ZILLZELL MEDIA PRIMA, 2024)
Gunungpayung Village possesses a rich history, culture, and traditions, yet it remains relatively unknown to many Indonesians. One of the village's profound traditions is the kenduri ceremony, reflecting the life and culture of the Javanese people. Kenduri is a traditional event held by the community to express gratitude, commemorate births or deaths, and partake in religious activities. This research aims to explore several aspects of the kenduri ceremony in Gunungpayung Village: its meaning, social, environmental, historical, and gastronomic aspects. The study employs a descriptive qualitative field research method. Findings reveal that kenduri, or selametan, encompasses various ceremonies marking significant events like births, deaths, religious celebrations, and the harvest season. The primary function of kenduri is to express gratitude to God, seek safety, and honor ancestors. It also promotes values such as solidarity, mutual cooperation, and togetherness within the community, fostering a harmonious atmosphere. Kenduri serves as a cultural ritual that enhances the sense of unity and kinship among local residents. The ceremony not only underscores the importance of communal bonds but also integrates environmental and historical elements, reflecting the village's deep-rooted traditions. Gastronomically, kenduri involves preparing and sharing traditional dishes, further enriching the cultural experience. In conclusion, the kenduri ceremony in Gunungpayung Village is a multifaceted tradition that encapsulates the essence of Javanese cultural practices. It plays a vital role in maintaining social cohesion, honoring heritage, and preserving the environmental and gastronomic aspects of the village's culture. Despite its significance, Gunungpayung Village and its kenduri tradition remain lesser-known, highlighting the need for broader recognition and appreciation.